2020
DOI: 10.1371/journal.pone.0229926
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of consensual stereotypes in moral foundations: A gender analysis

Abstract: The current study explored the accuracy of consensual moral stereotypes that women and men hold about each other, as well as whether the gender differences in morality found in previous literature replicate on a sample of Pakistani individuals. A sample of 300 was used with an equal number of men and women. Data from 50 of the respondents was collected online, whereas the rest was collected in person from universities. The 30-item Moral Foundations Questionnaire (MFQ30) was used as a measure of five Moral Foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 43 publications
(60 reference statements)
1
17
0
Order By: Relevance
“…Thus, it was understood that the girls in the data collection group had an individualistic, liberal and multicultural understanding. In the sub-dimensions of morality, where there was no difference between genders, it was seen that women again had higher scores (for a similar finding, see Niazi, Inam &Akhtar, 2020 andGraham et al, 2011). In many studies, women have a meaningful and higher means score than men in harm/care and fairness sub-factors.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Thus, it was understood that the girls in the data collection group had an individualistic, liberal and multicultural understanding. In the sub-dimensions of morality, where there was no difference between genders, it was seen that women again had higher scores (for a similar finding, see Niazi, Inam &Akhtar, 2020 andGraham et al, 2011). In many studies, women have a meaningful and higher means score than men in harm/care and fairness sub-factors.…”
Section: Discussionmentioning
confidence: 73%
“…For example, there are studies that find a difference in favor of women only in the factor of harm/care (Matsuo, Sasahara, Taguchi & Karasawa, 2019;Njus, Fawcett & Hazlett, 2016). Similarly, studies that find significant differences in favor of women in the factors of harm/care, fairness and purity/sanctity, and in favor of men in the factors of ingroup/loyalty and authority/respect (Niazi, Inam & Akhtar, 2020;Efferson & Glenn, 2018) were conducted. As a result, it could be said that women attach more importance to individual moral foundations than men, and men attach more importance to binding moral foundations (Sağel, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Females scored higher in purity, care, and fairness, and males in authority and loyalty. In contrast, Niazi et al (2020) showed there is a significant difference regarding care associated with females. This research was focused on a Pakistani sample comprising 300 male and female participants, and the MEQ was applied.…”
Section: Theoretical Backgroundmentioning
confidence: 83%
“…showing that females are more likely to have a preference for care than males (Gilligan 1983;Friesdorf 2015). Gender differences in the context of moral foundations preferences are controversial in the research, and the reason for this should be further investigated (Graham et al 2011;Jaffee & Hyde 2000;Atari et al 2020;Niazi et al 2020). This study has some limitations (i.e., conducted only in the Czech Republic, using nonparametric methods), and for this reason the findings cannot be generalized, and further studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…Combining these criteria, Table 1 lists the highly cited studies that repeatedly meet the inclusion criteria, including the following list of surveys and their respective publication citations. Athota et al 2019;Bespalov et al 2017;Boer and Fischer 2013;Cantarero et al 2018;Curry et al 2019;Dogruyol et al 2019;Du 2019;Feldman 2019;Graham et al 2012Graham et al , 2011Haidt 2013aHaidt , 2013bHaidt and Graham 2007;Joseph 2004, 2011;Haidt et al 1993;Hu 2017;Hu et al 2020;Iurino and Saucier 2020;Kim et al 2012;Kim and Kang 2013;Koleva et al 2016;Matsuo et al 2019;Mooijman et al 2018;Moreira et al 2019;Nechtelberger et al 2017;Nejat et al 2015;Niazi et al 2020;Nilsson and Erlandsson 2015;Ochoa et al 2016;Peker et al 2018;Purzycki et al 2018;Rahman 2015;Shim et al 2018;Shweder 1990;Shweder and Haidt 1993;Shweder et al 1997 Since the focus is on contemporary publications in the last decade, studies that originated before 2010 were included if a number of current publications continued to analyze the study's data within the 2010-2020 focus (e.g., WVS, ESS, EVS). However, studies that were primarily investigated prior to 2010, without numerous contemporary analyses were excluded.…”
Section: Systematic Phasementioning
confidence: 99%